A single birth dose of Hepatitis B vaccine induces polyfunctional CD4+ T helper cells - Strandmark, Julia; Darboe, Alansana; Diray-Arce, Joann; Ben-Othman, Rym; Vignolo, Sofia M.; Rao, Shun; Smolen, Kinga K.; Leroux-Roels, Geert; Idoko, Olubukola T.; Sanchez-Schmitz, Guzmán; Ozonoff, Al; Levy, Ofer; et al. (Frontiers in Immunology, 2022)
A single birth-dose of Hepatitis B vaccine (HepB) can protect newborns from acquiring Hepatitis B infection through vertical transmission, though several follow-up doses are required to induce long-lived protection. In addition to stimulating antibodies, a birth-dose of HepB might also induce polyfunctional CD4+ T-cells, which may contribute to initial protection. We investigated whether vaccination with HepB in the first week of life induced detectable antigen-specific CD4+ T-cells after only a single dose and following completion of the entire HepB vaccine schedule (3 doses). Using HBsAg- stimulated peripheral blood mononuclear cells from 344 infants, we detected increased populations of antigen-specific polyfunctional CD154+IL-2+TNFα+ CD4+ T-cells following a single birth-dose of HepB in a proportion of infants. Frequencies of polyfunctional T-cells increased following the completion of the HepB schedule but increases in the proportion of responders as compared to following only one dose was marginal. Polyfunctional T-cells correlated positively with serum antibody titres following the birth dose (day30) and completion of the 3-dose primary HepB vaccine series (day 128). These data indicate that a single birth dose of HepB provides immune priming for both antigen-specific B- and T cells